Raffaello Berti: arquiteto, compagno immigrato - Bernardo Santiago Hauck Teixeira (2020)
Raffaello Berti (1900 - 1972) stands as one of the most important architects in the history of Belo Horizonte. His contribution on design and construction of buildings for the city is exceptional by all means. However, his design process, extremely vast, complex and heterodox, is still very inaccessible and poorly publicized. This work aims on presenting this legacy, by a close look into his projects, looking for a reading key to this complexity, approaching the matter through the comprehension of modernity in Berti, and through the important historical phenomena of which he is part of: the european immigration to Brazil and the formation of italian communities in brazilian urban centers. We want to demonstrate how Berti developed a way towards design, with an early phase, and a maturation, which is obtained only through an intense and pragmatic workflow, which sources go back to his immigrant condition. Fare l‟America!